UTILIZACIÓN DE ALMIDÓN DE MALANGA (Colocasia esculenta L.) EN LA ELABORACIÓN DE SALCHICHAS TIPO FRANKFURT - ALBERTO LUIS TORRES RAPELO; PIEDAD MARGARITA MONTERO CASTILLO; LESBIA CRISTINA JULIO GONZÁLEZ (Biotecnología en el Sector Agropecuario y Agroindustrial, 2014)
Starch is an important ingredient in the food industry where it is used as a binder, thickener, gelling agent, agglutinant, humectant, and texturizer. It is also used in the manufacture of sausages and other cooked processed meats to give consistency to the product. This study aimed to evaluate the effect of substitution of wheat flour for taro starch (Colocasia esculenta L.) obtained from white and purple varieties on cooking losses and acceptability of a meat emulsion. To evaluate the cooking losses, three different formulations of Frankfurt sausages were prepared, in which wheat flour was replaced by 50%, 75% and 100% of taro starch and one control. To assess the acceptability of the products was used a taste panel untrained composed of 50 judges and a 5 points-hedonic scale was used. The results showed that all treatments with taro starch had lower cooking losses than the control product (p<0,05). Likewise, the incorporation of taro starch did not affect the acceptability of the meat product (p<0,05). We conclude that taro starch incorporated in the meat industry as filler and thickener in sausages is achievable.